Global Survey Reveals a Lack of Social Marketing Skills in the Conservation Sector and Shows Supply of Training Doesn't Meet Demand. (March 2019) - Robinson, Beth S.; Creasey, Matthew J. S.; Skeats, Ali; Coverdale, Imogen; Barlow, Adam
Biodiversity loss is one of the principle challenges facing us today. To halt and reverse this loss, conservation practitioners must find ways to change human behaviors which threaten species and ecosystems. Increasingly, it is being recognized that social marketing could be an effective way of achieving voluntary, ethical, and long-lasting behavior change for the benefit of biodiversity. By conducting a global survey of conservation practitioners, the objective of this study was to assess the need for social marketing skills, as well as the demand, supply, and barriers to receiving social marketing training in the conservation sector. From a sample of 322 conservation practitioners from 71 countries, results suggest there is a marked lack of social marketing skills in the conservation sector, with only 16.1% of participants considering their skill level to be expert or advanced. However, 61.5% of participants reported needing advanced or expert social marketing skills to be effective in their current role. In addition, the survey revealed a high demand for training in social marketing, but also that a lack of funds, time, and available courses all present major barriers to conservation practitioners receiving such training. The implications of these results for designing methods of providing conservation practitioners with social marketing skills and removing barriers are discussed.